DETERMINANTS OF THE ACCESS TO SOURCES OF FINANCE FOR SMALL AND MEDIUM ENTERPRISES (SMES) IN LIBYA: A CONCEPTUAL STUDY - Almbrok, Alhadi Abu; Ayedh, Abdullah Ahmed (PEOPLE: International Journal of Social Sciences, 2015)
The current study in general aimed to review the previous literature in regards to the determinants of access to finance for small and medium enterprises (SMEs) to derive relevant variables which make the actual impact for Business Owners to access to sources of finance. It also aimed to use such variables identified in previous research for developing a conceptual model and conducting an empirical field study on SMEs in the Libyan context.